Molecular and Kinetic Characterization of the Fermentative Behavior of Saccharomyces cerevisiae Strains Isolated from North Patagonia - Simes, Adriana Beatriz (2016)
At present, Argentina does not count with a production of indigenous yeast strains with suitable technological and oenological features to be used in the regional winery industry. Isolation and molecular characterization of these microorganisms and its fermentation attributes would be relevant to the sustainable development of the activity in the country and to recognize and preserve the biodiversity of the region. Eight strains isolated from grapes and musts from the North Patagonian region and genetically identified as Saccharomyces cerevisiae, were studied for their fermentation behavior, emphasizing in hexose transport through the plasma membrane, which is the limiting step of the process. Thus, sugar consumption profiles were analyzed in different media at laboratory scale, to be subsequently applied to the fermentation of natural musts. Three of the eight initial strains were selected, named ÑNM10, ÑIF8 and ÑMN16 according to their fermentation profiles. The expression of hexose transporters during fermentations revealed interesting differences in the response of each strain to sugar consumption, where transporters HXT2 and HXT5 showed significant changes in expression in Patagonian strains, which are normally associated to endurance to culture stress conditions. The results obtained by combining the characteristics studied, at molecular and physiological level, are extremely encouraging. Native strain ÑMN16, showed a high potential for application in local winemaking. Assays carried out on a pilot scale will determine the feasibility of applying this strain with promising technological features at industrial scale.